INVESTIGATION OF THE MONOLITHIC DIE BEARING LENGTH ON THE NON-UNIFORM STRAIN DURING THE LOW-CARBON WIRE PRODUCTION (Modern Problems of Metallurgy, 2024)
Low-carbon steel wire takes a large part in the production of wire products. The wire standards regulate the limits of its mechanical properties. Drawing non-uniform strain determines the mechanical properties. One of the main parameters determines the non-uniform strain is the die dimensions, specifically the length of the die bell and the length of the die bearing. Tool manufacturers provide appropriate recommendations for choosing the length of the die bearing depending on the wire diameter. In industry, the die bearing is bored to the required diameter size in worn out dies during previous drawing. Considering the constancy of the die length, this leads to a change in the ratio between the lengths of the die bell and die bearing and to a change in the level of non-uniform strain. The mechanical properties of the wire are determined mainly through the results of experimental investigations, it leads to significant costs of material and energy. In this work, using FEM computer simulation, the influence of the die bearing on the non-uniform strain while drawing 1030 steel wire with a diameter of 1.85 mm was investigated.